Leptospiral agglutinins in captive and free ranging non-human primates in Sarawak, Malaysia - Thayaparan, S.; Robertson, I. D.; Abdullah, M.T (Veterinary World, EISSN, 2014)
Aim:The proposed study was carried out to determine the extent of exposure to leptospirosis in non-human primates. Materials and Methods:Trapping of non-human primates was carried out opportunistically around the Bako National Park and the Matang Wildlife Center in the vicinity of human settlements and tourism areas of Sarawak. Blood samples were obtained from the saphenous vein to determine the presence of antibodies by the MicroscopicAgglutination Test (MAT) to 17 serovars of commonly found in Malaysia. Results:Trapping of non-human primates was carried out opportunistically around the Bako National Park and the Matang Wildlife Center in the vicinity of human settlements and tourism areas of Sarawak. Blood samples were obtained from the saphenous vein to determine the presence of antibodies by the MicroscopicAgglutination Test (MAT) to 17 serovars of commonly found in Malaysia. This study reports the screening of twelve primates (eight captive and four free ranging) for leptospirosis. Eight of the 12 monkeys (66.6%; 95% CI 34.9-90.1) reacted against one or two serovars of (Lai and Lepto175). Then serovar Lai is considered pathogenic for different mammals, including humans. Lepto 175 has been identified as an intermediate strain and further studies are being undertaken on this serovar. Conclusion: These results are important as primates may act as reservoirs of spp. for humans, which may potentially affect tourism (economic loss), conservation efforts and public health.